Radioactivity : introduction and history. - L'Annunziata, Michael F. (Elsevier, 2007)
Radioactivity: Introduction and Early History provides an introduction to radioactivity from natural and artificial sources on earth and radiation of cosmic origins. This book answers many questions for the layperson, student, teacher, and even practitioner as to the origins, properties, detection and measurement, and applications of radioactivity. Written at a level that most laypersons can appreciate, it includes many calculations that students and teachers may use in class work. Radioactivity: Introduction and Early History also serves as a refresher for experienced practitioners who use radioactive sources in his or her field of work. Also included are historical accounts of the major achievements of many famous pioneers and Nobel Laureates who have contributed to the science of radioactivity. * Provides entry-level overview of every form of radioactivity including natural and artificial sources, and radiation of cosmic origin. * Includes many solved problems to practical questions concerning nuclear radiation and its interaction with matter * Historical accounts of the major achievements of pioneers and Nobel Laureates, who have contributed to our current knowledge of radioactivity.